Effect of the Serious Illness Care Program in Outpatient Oncology: A Cluster Randomized Clinical Trial - Bernacki, Rachelle (JAMA Intern Med, 2019)
IMPORTANCE: High-quality conversations between clinicians and seriously ill patients about values and goals are associated with improved outcomes but occur infrequently. OBJECTIVE: To examine feasibility, acceptability, and effect of a communication quality-improvement intervention (Serious Illness Care Program) on patient outcomes. DESIGN, SETTING, AND PARTICIPANTS: A cluster randomized clinical trial of the Serious Illness Care Program in an outpatient oncology setting was conducted. Patients with advanced cancer (n = 278) and oncology clinicians (n = 91) participated between September 1, 2012, and June 30, 2016. Data analysis was performed from September 1, 2016, to December 27, 2018. All analyses were conducted based on intention to treat. INTERVENTIONS: Tools, training, and system changes. MAIN OUTCOMES AND MEASURES: The coprimary outcomes included goal-concordant care (Life Priorities) and peacefulness (Peace, Equanimity, and Acceptance in the Cancer Experience questionnaire) at the end of life. Secondary outcomes included therapeutic alliance (Human Connection Scale), anxiety (Generalized Anxiety Disorder 7 scale), depression (Patient Health Questionnaire 9), and survival. Uptake and effectiveness of clinician training, clinician use of the conversation tool, and conversation duration were evaluated. RESULTS: Data from 91 clinicians in 41 clusters (72.9% participation; intervention, n = 48; control, n = 43; 52 [57.1%] women) and 278 patients (45.8% participation; intervention, n = 134; control, n = 144; 148 [53.2%] women) were analyzed. Forty-seven clinicians (97.9%) rated the training as effective (mean [SD] score, 4.3 [0.7] of 5.0 possible); of 39 who received a reminder, 34 (87.2%) completed at least 1 conversation (median duration, 19 minutes; range, 5-70). Peacefulness, therapeutic alliance, anxiety, and depression did not differ at baseline. The coprimary outcomes were evaluated in 64 patients; no significant differences were found between the intervention and control groups. However, the trial demonstrated significant reductions in the proportion of patients with moderate to severe anxiety (10.2% vs 5.0%; P = .05) and depression symptoms (20.8% vs 10.6%; P = .04) in the intervention group at 14 weeks after baseline. Anxiety reduction was sustained at 24 weeks (10.4% vs 4.2%; P = .02), but depression reduction was not sustained (17.8% vs 12.5%; P = .31). Survival and therapeutic alliance did not differ between groups. CONCLUSIONS AND RELEVANCE: The results of this cluster randomized clinical trial were null with respect to the coprimary outcomes of goal-concordant care and peacefulness at the end of life. Methodologic challenges for the primary outcomes, including measure selection and sample size, limit the conclusions that can be drawn from the study. However, the significant reductions in anxiety and depression in the intervention group are clinically meaningful and require further study. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT01786811